The Influence of Politics on Architectural Thought A Descriptive and Analytical Study of the Effect of Political Ideology on the Achieved Architecture (Berlin City as an Example) (Journal of Engineering, 2012)
The research investigates the political effect and its directions on the architectural thoughts and its achievements and how can this political system affect all fields of life in communities including architectural urban design. The problem of the research lies in the ambiguity effects of the ideological national directions of the Nazi Party on the architecture and urban design of the city of Berlin, then determining the aims of the research to discuss the concepts of politics and architecture and their relation to the way of thinking that plays a role in the process of design that works on property and achieving the suitable urban environments for those communities. After that, the Nazi's party's thought would be studied and analyzed, its concepts, public beliefs and its relation with renewing the city of Berlin as an example, to finish with introducing the conclusions.